2007
DOI: 10.1016/j.bios.2006.06.027
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen tolerance of an implantable polymer/enzyme composite glutamate biosensor displaying polycation-enhanced substrate sensitivity

Abstract: Biosensors were fabricated at neutral pH by sequentially depositing the polycation polyethyleneimine (PEI), the stereoselective enzyme l-glutamate oxidase (GluOx) and the permselective barrier poly-ortho-phenylenediamine (PPD) onto 125-m diameter Pt wire electrodes (Pt/PEI/GluOx/PPD). These devices were calibrated amperometrically at 0.7 V versus SCE to determine the Michaelis-Menten parameters for enzyme substrate, l-glutamate (Glu) and co-substrate, dioxygen. The presence of PEI produced a 10-fold enhancemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 67 publications
(92 reference statements)
1
66
0
Order By: Relevance
“…PPD modified Pt electrodes are extensively utilised to improve selectivity of the polymer layer of both electrochemical sensors [6,17,[22][23][24] and biosensors [11,[25][26][27][28] since extracellular concentrations of certain metabolites are considered low in relation to the excessive concentration of AA. Therefore it is imperative that the integrity of the polymer is retained following implantation.…”
Section: Shelf-life Studies-effect Of Repeated Aa Calibrationsmentioning
confidence: 99%
See 1 more Smart Citation
“…PPD modified Pt electrodes are extensively utilised to improve selectivity of the polymer layer of both electrochemical sensors [6,17,[22][23][24] and biosensors [11,[25][26][27][28] since extracellular concentrations of certain metabolites are considered low in relation to the excessive concentration of AA. Therefore it is imperative that the integrity of the polymer is retained following implantation.…”
Section: Shelf-life Studies-effect Of Repeated Aa Calibrationsmentioning
confidence: 99%
“…Poly-o-phenylenediamine (PPD) can be integrated into the design of electrochemical sensors to function either as a conducting polymer [9] or more commonly as an insulating polymer [10,11]. Electropolymerisation of the monomer o-phenylenediamine (o-PD) in pH 7.4, deposits PPD in its insulating form onto the electrode surface [12].…”
Section: Introductionmentioning
confidence: 99%
“…Despite having multiple layers, the response time of this configuration was found to be good at ∼5 s. The Michaelis-Menten constants of J max and K M for the configuration were found to be 77 A cm −2 and 873 M (R 2 = 0.99, n = 21), respectively. The limit of detection (based on 3× SD of the baseline current) of this configuration was calculated to be ∼2.5 M glutamate, which is lower [ 47], who demonstrated that PPD-coated electrodes were highly efficient even at low oxygen concentrations, such as during ischaemia.…”
Section: Pt D /Ppd-bsa/pea/pei/gluox/ppd-bsamentioning
confidence: 99%
“…Using implantable sensors allows for stable, long-term recording of a number of common analytes in the extracellular fluid (ECF) of the brain including oxygen (Lowry et al, 1996Lowry and Fillenz, 2001;Bolger and Lowry, 2005), glucose (Hu and Wilson, 1997;Fillenz and Lowry, 1998a;Lowry et al, 1998a,b,c;Lowry and Fillenz, 2001;Dixon et al, 2002), nitric oxide (Brown et al, 2009) and glutamate (Kulagina et al, 1999;McMahon et al, 2006aMcMahon et al, , 2006bMcMahon et al, , 2007Qin et al, 2008;Tian et al, 2009). Unlike other methods implanted into the brain tissue (Clark et al, 1958;Krolicki and Leniger-Follert, 1980;Doppenberg et al, 1998;Gupta et al, 1999).…”
Section: Introductionmentioning
confidence: 99%